2015
DOI: 10.1021/acs.langmuir.5b01781
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Surfactants and Polyelectrolytes on the Interaction between a Negatively Charged Surface and a Hydrophobic Polymer Surface

Abstract: ABSTRACT:We have measured and characterized how three classes of surface-active molecules self-assemble at, and modulate the interfacial forces between, a negatively charged mica surface and a hydrophobic end-grafted polydimethylsiloxane (PDMS) polymer surface in solution. We provide a broad overview of how chemical and structural properties of surfactant molecules result in different self-assembled structures at polymer and mineral surfaces, by studying three characteristic surfactants: (1) an anionic aliphat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 48 publications
2
6
0
Order By: Relevance
“…The presence of steric repulsion in the presence of PFOA is well supported by the higher breakthrough curves observed in treated bacteria with PFOA in suspension (Figure a, solid squares and Table S1) compared with untreated bacteria (Figure a, solid triangles and Table S1)which is consistent with the adsorption test results (Figure S3), which indicate that greater PFOA adsorption occurs for treated bacteria relative to untreated bacteria. Previous studies also reported that the density of the adsorbed brush layers influences the steric repulsive force. , The result of interaction energy calculation at 10 mM NaCl is presented in Figure as a representative since a similar trend is observed in other conditions (Figure S1). The clear difference in the total interaction energy between the presence and absence of PFOA indicates that the addition of PFOA in cell suspensions increases the repulsive interaction between bacteria and quartz sand.…”
Section: Resultssupporting
confidence: 75%
“…The presence of steric repulsion in the presence of PFOA is well supported by the higher breakthrough curves observed in treated bacteria with PFOA in suspension (Figure a, solid squares and Table S1) compared with untreated bacteria (Figure a, solid triangles and Table S1)which is consistent with the adsorption test results (Figure S3), which indicate that greater PFOA adsorption occurs for treated bacteria relative to untreated bacteria. Previous studies also reported that the density of the adsorbed brush layers influences the steric repulsive force. , The result of interaction energy calculation at 10 mM NaCl is presented in Figure as a representative since a similar trend is observed in other conditions (Figure S1). The clear difference in the total interaction energy between the presence and absence of PFOA indicates that the addition of PFOA in cell suspensions increases the repulsive interaction between bacteria and quartz sand.…”
Section: Resultssupporting
confidence: 75%
“…Electrostatic repulsion explains the negligible adsorption of negatively charged SDS on hydrophilic silica below the CMC (Figure S4). Increased SDS adsorption with an increase in SDS concentration on a hydrophilic surface could be caused by electrostatic screening of the charges in the presence of counterions (Na + ) in solution. ,, However, most of the mass gains are explained by the hydration water, which correlated with the observed high dissipation.…”
Section: Resultsmentioning
confidence: 99%
“…Although −CH 3 surfaces have no specific charge, interaction of water with the aliphatic chain of the SAM could lead to a slightly negative charge over the surface. It has been reported that air bubbles, oily groups, and hydrophobic surfaces spontaneously acquire a diffuse negative charge in water as a result of hydroxide ion adsorption. This behavior is a result of suppression of the dipole moment of water molecules, which induces an increase in hydroxide ion affinity to surfaces where dipole moment fluctuations are smaller than in bulk water .…”
Section: Resultsmentioning
confidence: 99%